2001
DOI: 10.1002/pola.1267
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of novel basic polysulfone polymers

Abstract: Two synthesis routes for the preparation of novel base-modified polysulfones (PSUs; Udel) were investigated: (1) the addition of the basic aromatic ketones 2,2Ј-dipyridylketone and 4,4Ј-bis-(diethylamino)benzophenone and the basic aromatic aldehydes N,N-dimethylamino-benzaldehyde, pyridine-2-aldehyde, pyridine-3-aldehyde, and pyridine-4-aldehyde to lithiated PSU and (2) the reaction of lithiated PSU with basic aromatic carboxylic acid esters such as 4-N,N-dimethylaminobenzoic acid ethylester, pyridine-2-carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 18 publications
(21 reference statements)
0
51
0
1
Order By: Relevance
“…A likely reason for the lower than expected DS is steric hindrance of the electrophilic around the sulfone linkage because the electrophilic carbon center is not easily accessible. 46 Another reason could be side reactions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A likely reason for the lower than expected DS is steric hindrance of the electrophilic around the sulfone linkage because the electrophilic carbon center is not easily accessible. 46 Another reason could be side reactions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In our work on polysulfone modification by lithiation, [7][8][9][10][11]46 we and others have demonstrated that this synthetic method is an effective approach to postfunctionalized PSf with a wide variety of functional groups. Reaction of various electrophilic aryl and alkyl carbonyl compounds with PSf-Li yields the corresponding carbinol substituents, 9−11 including those containing arylamines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Basic polymers are typically PBI, but other polymers such as poly(4-vinylpyridine) (P 4 VP) [143], aminated PSF [144,145] and PEEK [146] and pyridine containing polymers [91,92] have also been used. The acidic polymers are typically sulphonated polysulphone (SPSF) [147,148], sulphonated polyetheretherketone (SPEEK) [149], sulphonated poly(2,6-dimethyl-1,4-phenylene oxide) (SPPO [150]), sulphonated poly(arylene thioether)s [151], and sulphonated poly[bis(phenoxy)phosphazene] (SPOP [152]).…”
Section: Ionic Cross-linkingmentioning
confidence: 99%
“…proton channels 22 and pumps 23 ), carbon nanotubes, 24 and PEMs. [25][26][27][28][29][30][31][32] Clearly, an understanding of both the common (i.e. in the formation of a continuous network of dynamical hydrogen bonds and the excess protonic charge following the center of symmetry of the hydrogen bond coordination) and distinct features in the molecular details of proton movement in these systems will prove helpful in the development of highly conductive PEMs.…”
Section: Introductionmentioning
confidence: 99%